Avaliação em tomografia computadorizada por feixe cônico da quantidade de tecido ósseo de suporte, vestibular e lingual, dos incisivos centrais superiores e a relação com suas inclinações - Brandão , Aluana de Siqueira (2012)
The present study evaluated, by means of Cone Beam Computed Tomography (CBCT), the amount of supporting bone tissue, vestibular and lingual, in the upper central incisors (teeth 11 and 21) and the relationship with their dental inclinations (1.PP). The sample consisted of 30 images obtained by CBCT, belonging to adult patients, between 20 and 47 years old, of both genders, who hadn’t previously undergone to orthodontic treatment. It was evaluated the amount of bone tissue, in the third apical (apical vestibular thickness/ABT and apical lingual thickness/ALT), medium (medium vestibular thickness /MBT and medium lingual thickness/MLT) and cervical (cervical vestibular thickness/CBT and cervical lingual thickness/CLT). It was used the statistical test of Pearson correlation, Linear Regression and the analysis of variance (P<0,005). According to the results, it was found significant positive linear correlation between EVA and 1.PP to the theeth 11 and 21, that is to say, the more the values of 1.PP increase, the more the values of the EVA increase for the teeth 11 and 21. For each one of the six variants it was done a model of simple linear regression, it was also noticed that the variants. EVA (p=0,034) for the tooth 11 and EVA (p=0,009) for the tooth 21 are significantly positive coefficient, but with low values of the coefficient of determination (12,0% for the tooth 11 and 19,2%for the tooth 21), indicating that the variants were not enough to explain the variability of 1.PP. In the vestibular face, it were found significant differences between the regions (P<0,001). The medium amount of bone was significantly greater for the apical region comparison to the others. For the lingual face it were found significant differences just between the regions (P<0,001). It was concluded that there isn’t any relation between the amount of bone tissue and the dental inclination of the superior incisors supporting, this way, the assumption that the individual anatomical variation must be taken into consideration in plans that require dental inclination and translational moviments